Geospatial Visualisation - Moore, Antoni.; Drecki, Igor. (Lecture Notes in Geoinformation and Cartography, 2013)
This book is a selection of chapters evolved from papers on completed research submitted to GeoCart2010 / the 1st ICA Regional Symposium on Cartography for Australasia and Oceania, held in Auckland, New Zealand, 1st -3rd September 2010. All of the chapters have been updated and revised thoroughly. They have been blind peer reviewed by two referees of international research standing in geospatial science, mostly in the subdisciplines of cartography and geovisualisation. The book features cutting edge topics such geovisual analytics, mobile / Web 2.0 mapping, spatiotemporal representation, cognitive cartography, historical mapping and 3D technology.